2012
DOI: 10.1097/lgt.0b013e3182410544
|View full text |Cite
|
Sign up to set email alerts
|

Vulvar Intraepithelial Neoplasia

Abstract: Excisional treatment has diagnostic and treatment advantages in VIN lesions. The goal is to prevent development of invasive vulvar cancer while preserving normal vulvar anatomy and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Despite treatment, VIN recurrence rate ranges from 6% to 50% post treatment, 14,100–121 and it is influenced by margins status, duration of follow-up, patient-related factors (multifocality of disease, immunosuppression, and smoking), and VIN type (even if disease outcome between VHSIL and dVIN is not always detailed). In addition, methodological limitations and statistical analysis differences between studies contribute to the wide range reported.…”
Section: Methodsmentioning
confidence: 99%
“…Despite treatment, VIN recurrence rate ranges from 6% to 50% post treatment, 14,100–121 and it is influenced by margins status, duration of follow-up, patient-related factors (multifocality of disease, immunosuppression, and smoking), and VIN type (even if disease outcome between VHSIL and dVIN is not always detailed). In addition, methodological limitations and statistical analysis differences between studies contribute to the wide range reported.…”
Section: Methodsmentioning
confidence: 99%
“…As the incidence of premalignant vulvar lesions has increased in recent decades, especially in younger women, is it the knowledge of aetiopathology and risk factors that determines its management [114]. The purpose of treatment for vulvar precursor lesions is to relieve symptoms, prevent cancer progression, and preserve anatomy and organ function [126]. The currently preferred treatment modality for HSIL/uVIN or dVIN is surgical excision, or skinning vulvectomy [127].…”
Section: Current Treatment Of the Diseasementioning
confidence: 99%